2020
DOI: 10.3390/s20185051
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Vehicle Detection and Classification Methodology Using Strain Sensors under Bridge Deck

Abstract: Vehicle detection and classification have become important tasks for traffic monitoring, transportation management and pavement evaluation. Nowadays there are sensors to detect and classify the vehicles on road. However, on one hand, most sensors rely on direct contact measurement to detect the vehicles, which have to interrupt the traffic. On the other hand, complex road scenes produce much noise to consider when to process the signals. In this paper, a data-driven methodology for the detection and classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…with minimal capital consumption and time consumption before traveling [18]. It is found that the research on the intelligent recommendation of tourism information in academic circles began at the beginning of this century [19]. Figure 1 describes the basic flow of user personalization model creation.…”
Section: Personalized Recommendationsmentioning
confidence: 99%
“…with minimal capital consumption and time consumption before traveling [18]. It is found that the research on the intelligent recommendation of tourism information in academic circles began at the beginning of this century [19]. Figure 1 describes the basic flow of user personalization model creation.…”
Section: Personalized Recommendationsmentioning
confidence: 99%
“…In particular, the shadow is a common barrier that makes it difficult to correctly identify backgrounds and objects [5]. The presence of a shadow can lead to a *Corresponding Author Email: hfarsi@birjand.ac.ir (H. Farsi) recognition error, and the object can be identified as a larger object [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Wi-Fi channel state information [14] has also been used to provide similar non-contact traffic monitoring. Strain measurements [15] and vibration sensing [16] have been shown to provide vehicle detection and classification information.…”
Section: Introductionmentioning
confidence: 99%